Immune‐suppressive effects of interleukin‐6 on T‐cell‐mediated anti‐tumor immunity - Tsukamoto, Hirotake (Cancer Sci, 2017)
Accompanied by the growing clinical applications of immunotherapy in the treatment of cancer patients, development of novel therapeutic approaches to reverse the immune‐suppressive environment in cancer patients is eagerly anticipated, because the success of cancer immunotherapy is currently limited by immune‐suppressive effects in tumor‐bearing hosts. Interleukin (IL)‐6, a pleotropic proinflammatory cytokine, participates in tumor cell‐autonomous processes that are required for their survival and growth, and is therefore known as a poor prognostic factor in cancer patients. In addition, an emerging role of IL‐6 in modulating multiple functions of immune cells including T cells, dendritic cells, and macrophages is responsible for the dysfunction of innate and adaptive immunity against tumors. Therefore, the IL‐6‐targeting approach is of value as a promising strategy for desensitization and prevention of immune‐suppressive effects, and should be an effective treatment when combined with current immunotherapies. The aim of the present review is to discuss the immune‐suppressive aspects of IL‐6, notably with modification of T‐cell functions in cancer patients, and their relationship to anti‐tumor immune responses and cancer immunotherapy.